Implementation of Management Information Systems to Enhance Educational Quality: (Case Study at SMP Negeri 11 Lhokseumawe) - Muhammad Ilham; Yuniarti, Yuniarti (Idarah (Jurnal Pendidikan dan Kependidikan), 2022)
The context for this study is that people continue to have negative perceptions of the quality of education services. As a result, efforts must be made to improve the quality of educational services. The implementation of an IT-based Management Information System is projected to aid in the improvement of educational services. The goal of this study is to be able to implement a school management information system in order to eliminate the hurdles encountered so that the process of implementing a school management information system in order to improve the quality of education services can be carried out effectively. This study employs a descriptive method with a qualitative approach. The study's resource people included school administrators, teachers, TU heads, operators, students, parents, and members of the community. Schools can provide speedier and more effective educational services to service consumers by implementing a management information system. The findings revealed that the school information system used was evaluated in terms of goals (goals), inputs (inputs), processes (processes), and outputs (outputs), which could aid in the implementation of school management information systems in improving the quality of education services at SMP Negeri 11 Lhokseumawe. Both in terms of people resources, facilities, and infrastructure, as well as financial resources. Meanwhile, for the management of teacher data, student data, sarpras data, student education fee payment data, and attendance system, human resource knowledge, HR goals and priorities, student availability, school management support, the existence of structures and schedules, and the implementation of educator content and capabilities are all carried out.